2011
DOI: 10.1111/j.1525-139x.2011.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

Home Hemodialysis in the Remote Canadian North: Treatment in Manitoba Fly‐in Communities

Abstract: Manitoba has the highest prevalence of ESRD in Canada. Northern Manitoba is a very sparsely settled area with a high proportion of aboriginal ESRD patients. Relocating to urban areas for dialysis is psychosocially and culturally stressful to patients. Delivering dialysis care in a home setting has demonstrated advantages in both clinical, economic, and health related quality of life domains. Establishing home hemodialysis in very remote communities has significant challenges, including poor and inadequate hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Seven articles directly addressed the barriers created by travel and delivery costs to northern regions [6,23,27,28,34,43,44]. Low population density and communities scattered over vast geographical distances contribute to costly transportation [43].…”
Section: Travel and Delivery Costsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven articles directly addressed the barriers created by travel and delivery costs to northern regions [6,23,27,28,34,43,44]. Low population density and communities scattered over vast geographical distances contribute to costly transportation [43].…”
Section: Travel and Delivery Costsmentioning
confidence: 99%
“…Low population density and communities scattered over vast geographical distances contribute to costly transportation [43]. In order to service these large areas, higher costs are required for patient and healthcare provider travel and for the delivery of medical supplies and equipment [27,43,44]. It was found that particularly within North America, increased use of air travel was common and expensive [6,27].…”
Section: Travel and Delivery Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…The issue then turns to practical aspects of intensive hemodialysis provision. Zacharias et al (17) describe strategies to make home hemodialysis accessible to patients living in geographically isolated communities in northern Manitoba, Canada. The unprecedented success of intensive and home hemodialysis in Australia and New Zealand is chronicled by Agar et al (18).…”
mentioning
confidence: 99%